Teka-Teki Logika untuk Meningkatkan Minat Belajar Siswa Sanggar Kegiatan Belajar Balikpapan Timur - Ryan Angga Pratama; Ari Musdolifah (Abdimas Universal, 2019)
The success of mathematics learning is supported by the teacher's proficiency in carrying out teaching activities and awareness of students in participating in learning activities. Therefore, learning requires the ability of teachers to manage learning and / or their ability to manage classes. Teachers must have capable skills in the fields of strategy and learning models that vary. For this reason, it is necessary to have active, fun, creative learning, and be able to provide attraction so that students can express themselves in learning and experience no saturation, so students can understand the material well. In learning activities, one way that can be done by teachers to overcome these problems is to provide a learning that is able to optimize the logic of students' thinking in solving non-routine problems in school, namely Mathematical Logic Puzzle. Through the provision of challenge questions in the form of Mathematical Logic Puzzles, students gain knowledge and understanding of mathematical logic puzzles, gain new learning experiences, dare to express ideas and be able to answer various kinds of non-routine problems and problems of logic related to life everyday, and students are more motivated in learning mathematics. Keywords: mathematical logic puzzles, mathematics learning